Effects caused by water-soluble chitosans with high molecular weight in bacterial and mammal membrane models using Langmuir monolayers - Jochelavicius, Karen (2022)
Lipid monolayers are well-known systems that mimic cell membrane environments, being used in a variety of studies involving molecules that affect the membrane structure. Incorporation of chitosans into lipid monolayers is known to cause expansion and, mostly, fluidization, having stronger effects on negatively charged monolayers and with low molecular weight chitosans. These effects are attributed to a combination of electrostatic and hydrophobic interactions, correlating well with the stronger interactions with the negatively charged bacterial cell membranes than for mammalian membranes. In this thesis, we shall present results that challenge these interpretations. First, we employ water-soluble chitosans that induce larger effects on zwitterionic phospholipids, namely dipalmitoyl phosphatidyl ethalonamine (DPPE) and dipalmitoyl phosphatidyl choline (DPPC), than on negatively charged dipalmitoyl phosphatidyl glycerol (DPPG). Slightly stronger effects are induced on the lipid extract of Escherichia coli (E. coli), except when compared to DPPE on acetate buffer. Even more relevant is the effect induced on monolayers prepared with a ternary mixture of DPPC, cholesterol (Chol) and sphingomyelin (SM) (SM-DPPC-Chol), which represents lipid rafts, for which effects appear at chitosan concentrations that are orders of magnitude smaller than reported in the literature for other chitosans or types of monolayer. The differences from the literature may be attributed to the high acetylation degree of one of the chitosans used, named Ch35% as it has a 35% acetylation degree. The charge in Ch35% was not sufficient for the electrostatic interactions to predominate over the hydrophobic interactions. The importance of charge availability for such interactions was confirmed by the larger monolayer expansion induced by Ch15%, a chitosan with 15% acetylation degree. Because both chitosans were water soluble, experiments could be made with subphases at physiological pH and at an acidic pH. Ch35% tend to have larger effects on monolayers deposited on the acidic pH, with a few exceptions when the larger volume occupied by the chitosan at a high pH led to larges expansions. Surprisingly, Ch15% induced larger effects on physiologic pH when incorporated in E. coli lipids, and this remains an open point. Also worth mentioning is that Ch35% and Ch15% have high molecular weights, ca. 106 g mol1, and still produced stronger effects than low molecular weight chitosans in previous studies, again contradicting expectations from the literature. In one hand, the larger effects induced on lipid rafts than on E. coli lipid extract calls for caution in the possible use of chitosans as bactericide agent; on the other hand, we observed a significant effect of Ch35% on monolayers of lipopolysaccharides (LPS), which represent the external wall of Gram-negative bacteria. Taken together, the results presented here indicate that charge availability and distribution in chitosans are probably the most important factor for their interaction with Langmuir monolayers, and the findings related to physiological pH and lipid rafts require a thorough revisit of studies on cell membrane models.